2018
DOI: 10.1097/iae.0000000000001786
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Vascular Arcade Width and Angle in High Axial Myopia

Abstract: Axial elongation was correlated with decreasing angle kappa, caused by an elongation of the disk-foveola distance because of an enlargement of the gamma zone, whereas VDA remained constant. By contrast, horizontal length of macular Bruch membrane and vertical length of macular Bruch membrane were independent of axial elongation. Axial elongation did not lead to lengthening of Bruch membrane in the macular region in eyes without macular chorioretinal lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 27 publications
3
22
0
Order By: Relevance
“…Previous histological investigations revealed that the axial myopic elongation led to an enlargement of the eye mainly in the posterior ocular segment, starting at or behind the equator and being more pronounced the closer to the The elongation of the DFD (mean: 1.16 AE 0.34 mm) in the adolescent children of our study population was mainly due to an increase in gamma zone width (+300% or 0.29 AE 0.30 mm) as compared to an increase in macular BM length (+18% or 0.74 AE 0.21 mm). This observation was in agreement with findings obtained in adults in whom the length of macular BM was mostly independent of axial length and in whom the axial elongation-related increase in DFD was mostly due to the enlargement of parapapillary gamma zone (Jonas et al 2011a(Jonas et al , 2015a(Jonas et al , 2017a.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Previous histological investigations revealed that the axial myopic elongation led to an enlargement of the eye mainly in the posterior ocular segment, starting at or behind the equator and being more pronounced the closer to the The elongation of the DFD (mean: 1.16 AE 0.34 mm) in the adolescent children of our study population was mainly due to an increase in gamma zone width (+300% or 0.29 AE 0.30 mm) as compared to an increase in macular BM length (+18% or 0.74 AE 0.21 mm). This observation was in agreement with findings obtained in adults in whom the length of macular BM was mostly independent of axial length and in whom the axial elongation-related increase in DFD was mostly due to the enlargement of parapapillary gamma zone (Jonas et al 2011a(Jonas et al , 2015a(Jonas et al , 2017a.…”
Section: Discussionsupporting
confidence: 92%
“…These findings confirmed results obtained in the previous crosssectional and population-based Beijing Eye Study, in which a longer DFD was correlated with longer axial length (Jonas et al 2011a). This observation was in agreement with findings obtained in adults in whom the length of macular BM was mostly independent of axial length and in whom the axial elongation-related increase in DFD was mostly due to the enlargement of parapapillary gamma zone (Jonas et al 2011a(Jonas et al , 2015a(Jonas et al , 2017a. Previous histological investigations revealed that the axial myopic elongation led to an enlargement of the eye mainly in the posterior ocular segment, starting at or behind the equator and being more pronounced the closer to the The elongation of the DFD (mean: 1.16 AE 0.34 mm) in the adolescent children of our study population was mainly due to an increase in gamma zone width (+300% or 0.29 AE 0.30 mm) as compared to an increase in macular BM length (+18% or 0.74 AE 0.21 mm).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It may be due to a parapapillary gamma zone-associated lengthening of the retinal nerve fibers, since gamma zone increases the disc-fovea distance [ 43 , 45 , 46 ]. Since the distance between the temporal superior arterial arcade and the temporal inferior arterial arcade is not affected by axial elongation in eyes without macular BM defects, the angle between the temporal arterial arcades decreases with longer axial length [ 100 ].…”
Section: Main Textmentioning
confidence: 99%